Sources of error in AC measurement of skin conductance - G.Martinsen Ørjan; Pabst Oliver; Tronstad Christian; Grimnes Sverre (Journal of Electrical Bioimpedance, 2015)
Alternating current methods have the potential to improve the measurement of electrodermal activity. However, there are pitfalls that should be avoided in order to perform these measurements in a correct manner. In this paper, we address issues like the choice of measurement frequency, placement of electrodes and the kind of electrodes used. Ignoring these factors may result in loss of measurement sensitivity or erroneous measurements with artifacts that contain little or no physiological information.